ANALYZING POLYGAMY REQUIREMENTS IN INDONESIA BY READING WOMEN IN TEXT AND CULTURE - Murniati Murniati; Henry Agus Sulistiyono; Wahidullah Wahidullah (JICSA : Journal of Islamic Civilization in Southeast Asian, 2020)
This paper discusses re-conception of the requirements of polygamy marriage in Indonesia. It is expected to reach a fair for husband, wife, and children as well as to achieve the spirit of marriage goals. Juridical normative research methods are used to see injustice in the requirements of polygamy in UUP No.1 of 1974, namely 3, 4, and 5, and which do not correlate with Article 1 of that law. The research suggests that the understanding the text as well as patriarchal culture are the leading contributors to the injustice and must be resolved, so the dignity of marriages that is beneficial by protecting the parties without discrimination and humanity can be realized.